Single-Camera Guidewire Movement Tracking System in a Concentrically Occluded Configuration for an Endovascular Interventions Simulator Interface - Harun, Hazwani; Ramli, Hafiz Rashidi; Saripan, M. Iqbal; Safri, Lenny Suryani; Harunarashid, Hanafiah (International Journal of Integrated Engineering, 2026)
Endovascular intervention simulator is a training device for image-guided procedures involving instruments such as guidewires and catheters inserted percutaneously into blood vessels.  The efficiency of the simulator relies on the accuracy of its tracking system in estimating the motion of these instruments. Detecting the movement of the guidewire is challenging because it is positioned inside the catheter. To address this, custom markers were developed on the guidewire's surface, and the Gunnar Farneback Algorithm Method was applied to detect its movement. Firstly, a camera records the guidewire's movements. The Gunnar Farneback Algorithm Method then processes the extracted images to obtain raw magnitude and orientation data. This output data was analyzed to get its accuracy and thus validated by comparing experimental values with theoretical values. The results show that the developed tracking system can estimate the distance of the guidewire's movement with an accuracy of 94.43% and 64.80% for the direction. These findings demonstrate that the developed tracking system is effective and sufficient in detecting the movement of a guidewire inside the catheter.